Dampak Bentuk Pembelajaran Kooperatif Tipe Jigsaw Dan Motivasi Belajar Terhadap Prestasi Belajar di Universitas Bhayangkara - Onny Siagian, Ade (INSPIREE: Indonesian Sport Innovation Review, 2021)
The purpose of the study. To find out: a) The effect of the Jigsaw cooperative learning bentuk on learning achievement in sports physiology. b) The influence of motivation on learning achievement in Sports Physiology. c) The interaction between the Jigsaw cooperative learning bentuk and motivation on learning achievement in Sports Physiology. Materials and methods. The population was students of the Department of Sport Science and Sports Coaching, Faculty of Sports and Health, Bhayangkara University Greater Jakarta. The sample is the third semester students consisting of two classes, namely class A as treatment and class B as control. Because the population is small, there is no sampling. Data collection techniques using motivation questionnaires and learning achievement tests. The data analysis technique used two-way analysis of variance. Results. The results The results of the analysis a) The learning achievement of students taught with the Jigsaw cooperative learning bentuk (mean = 60.81) was better than students taught with the conventional bentuk (mean = 60.21) obtained a statistical value of 7.234 with a significance of 0.002. b) The learning achievement of students with high motivation (mean = 71.05) is better than students who study with low motivation (mean = 50.00) obtained a statistical value of 146.905 with a significance of 0.000. c) There is an interaction of influence between learning bentuks and motivation in increasing learning achievement in the Sports Physiology course, the statistical value is 12.342 with a significance of 0.001. Conclusions. So from the results of this study it can be concluded that the Jigsaw type of cooperative learning bentuk is better than the conventional bentuk, and high learning motivation is better than low learning motivation